Returns to Office in National and Local Politics - Kaisa Kotakorpi; Panu Poutvaara; Marko Terviö (Center for Economic Studies and ifo Institute (CESifo), 2013)
We study the returns to political office using data from Finnish parliamentary elections in 1970-2007 and municipal elections in 1996-2008. The discontinuity of electoral outcomes in individual candidate votes allows us to estimate the causal effect of being elected on subsequent income. Getting elected to parliament increases annual earnings initially by about 20,000, but most of this effect fades out over time. Getting elected to a municipal council has a positive effect of about 1,000 on subsequent annual earnings.
Keywords: D72; 330; returns to office; elections; regression discontinuity